Attitudes towards the treatment of nausea and vomiting in pregnancy: results from a nationwide online study in Germany - Mangler, Mandy; Kuhlmann, Kirsten; Kohlhepp, Florian; Steeb, Theresa; Paulus, Wolfgang E. (Frontiers in Global Women's Health, 2025)
BackgroundNausea and vomiting in pregnancy (NVP) affect up to 85% of pregnant individuals, predominantly in the first trimester. While most cases are mild, moderate to severe NVP can significantly impair quality of life and require medical intervention. Besides, safety concerns often influence decision-making. This study examines the perceptions, concerns, and information-seeking behaviors of women in Germany regarding NVP and its treatment.MethodsA nationwide cross-sectional online study was conducted from March 18–28, 2024, targeting pregnant individuals and mothers in Germany via the “Echte Mamas” online community. Participants completed an anonymous online questionnaire comprising 15 items covering sociodemographic data, NVP severity (using the PUQE-24 score for pregnant individuals currently suffering from NVP), treatment attitudes, and information-seeking behavior. Data were analyzed using descriptive statistics and subgroup analyses were performed to investigate differences in NVP severity.ResultsAmong 506 respondents (completion rate: 83.9%), 81.9% reported experiencing NVP, with 40% reporting moderate, 30.6% mild and 29.4% severe symptoms. Hospitalization was required in 12.4% of cases, predominantly among those with severe NVP, with 76.3% of those receiving medication post-discharge. Participants primarily sought information from physicians (53.4%), the internet (50.6%), and midwives (44.5%), with more severe NVP prompting greater information-seeking behavior. Safety concerns dominated treatment preferences, with participants prioritizing drug approval (on-label prescription) for pregnancy and rapid symptom relief.ConclusionThis study emphasizes the need for proactive communication from healthcare providers about safe and effective NVP treatments. Tailored, patient-centered strategies that address safety concerns and provide evidence-based guidance are essential for informed decision-making.